Methyl Canthin-6-one-2-carboxylate Inhibits the Activation of the NLRP3 Inflammasome in Synovial Macrophages by Upregulating Nrf2 Expression - Yuanyuan Chen; Zongying Zhang; Yuan Yao; Xiaorong Zhou; Yong Ling; Liming Mao; Zhifeng Gu (Current Issues in Molecular Biology)
Rheumatoid arthritis (RA) is an autoimmune disorder that leads to severe cartilage deterioration and synovial impairment in the joints. Previous studies have indicated that the aberrant activation of the NLRP3 inflammasome in synovial macrophages plays a significant role in the pathogenesis of RA and has been regarded as a therapeutic target for the disease. In this study, we synthesized a novel canthin-6-one alkaloid, namely methyl canthin-6-one-2-carboxylate (Cant), and assessed its effects on NLRP3 inflammasome activation in macrophages. Our data reveal that exposure to Cant significantly suppressed the transcription and secretion of multiple pro-inflammatory mediators, including IL-1β, IL-6, IL-18, TNF-α, NO, and COX2, in a dose-dependent manner. These alterations were associated with changes in the activation of various signaling pathways, including NF-kB, MAPK, and PI3K-AKT pathways. Notably, pretreatment with Cant significantly reduced LPS/ATP-induced activation of the NLRP3 inflammasome, as evidenced by the decline in the cleaved forms of IL-1β and caspase-1 in cell culture supernatants of BMDMs. Regarding the mechanisms, our data show that Cant could enhance the expression of Nrf2 in macrophages, which play an inhibitory role in ROS production. Collectively, our data demonstrate that Cant might suppress the activation of the NLRP3 inflammasome by upregulating the production of Nrf2, suggesting that Cant could serve as a candidate for the further development of anti-RA drugs.